Vibration isolation performance of a vehicle suspension system using dual dynamic dampers - Hazra S.; Ghosh M.K. (My University, 2025)
Vibration isolation performance of a vehicle system using dual dynamic dampers has been investigated. A quarter car and full car suspension system using dual dynamic dampers have been modeled for investigation. The dampers are placed on sprung mass and un-sprung mass respectively for investigation of vibration isolation performance of the passenger cabin from ground motion and road holding capacity i.e., the stability of vehicle. It is seen that a full car suspension system featuring dual dynamic dampers can substantially improve the ride comfort and road holding capacity. © Krishtel eMaging Solutions Private Limited 2009.